(untitled) (Web of Teachers: Inderscience Research, 2024)
The Jadid movement appeared in Uzbekistan at the beginning of the 20th century, that is, at the beginning of the 1900s. This movement is mainly aimed at the renewal of the Uzbek nation, development of culture and education. Jadid’s means "renewal", which was one of their goals, which was to renew old traditions and absorb modern knowledge and culture.